Layered oxide material with high cycle stability and preparation method and application thereof

By preparing a layered sodium ion precursor and carrying out a Li+/Na+ substitution reaction, the problem of lithium-nickel mixing in the high-temperature synthesis of cobalt-free lithium-ion battery cathode materials was solved, achieving high cycle stability and structural stability of the material and overcoming the temperature sensitivity and process instability of traditional methods.

CN120998994APending Publication Date: 2025-11-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511137053.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies for preparing cobalt-free lithium-ion battery cathode materials suffer from severe lithium-nickel mixing, structural instability, and poor cycle performance. In particular, it is difficult to control cation mixing during high-temperature synthesis, resulting in poor material performance.

Method used

The process involves first synthesizing a layered sodium ion precursor, NaNixMn1-xO2, and then performing Li+/Na+ replacement via molten salt ion exchange, solid-phase or liquid-phase ion exchange methods to prepare LiNixMn1-xO2 material. By utilizing the large radius of Na+ to block Ni2+ migration, and by controlling the molar ratio of Li/Na and the temperature, directional control of ion migration can be achieved, thereby reducing lithium-nickel mixing.

Benefits of technology

This effectively suppresses lithium-nickel mixing, improves the structural stability and cycle performance of the material, reduces the synthesis difficulty, and achieves a cobalt-free lithium-ion layered oxide cathode material with high cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120998994A_ABST
    Figure CN120998994A_ABST
Patent Text Reader

Abstract

The invention relates to a layered oxide material with high cycle stability and a preparation method and application thereof, the chemical formula of the layered oxide material is LiaNabNixMn (1-x) O2, 0 lt; xlt; 0.90 < = a < = 1, 0 < = b < = 0.1; the preparation method comprises the following steps: preparing a layered oxide precursor NaNi < x > Mn < 1-x > O < 2 >; mixing the precursor with a first lithium source, and then carrying out lattice site Li < + > / Na < + > replacement by at least one of molten salt ion exchange, solid phase ion exchange and liquid phase ion exchange to obtain an intermediate; cleaning the intermediate, performing solid-liquid separation, and drying to obtain a layered oxide material with high cycle stability; the layered oxide material is prepared through lattice site selective Li < + > / Na < + > replacement reaction, so that the obtained material has excellent cycling stability and specific capacity, and the method is simple in process, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a lithium battery cathode material, and more particularly to a layered oxide lithium battery cathode material with high cycle stability, its preparation method, and its application. Background Technology

[0002] As a core energy storage technology supporting the national "dual-carbon" strategy, lithium-ion batteries urgently need to meet the dual demands of high energy density and low cost for new energy vehicles in their cathode material development. Currently, the mainstream ternary layered oxide LiNi... x Co y Mn 1-x-y O2(NCM) faces inherent bottlenecks in high-temperature solid-state synthesis: on the one hand, during the sintering process, Li... + Migration to the transition metal layer causes severe lattice Li + / Ni 2+ Cation mixing (antisite defects ≥8%) leads to blockage of ion diffusion channels and deterioration of the cycle structure. On the other hand, although Co can inhibit mixing and maintain structural order, as a strategically scarce metal (with an abundance of only 0.0025% in the Earth's crust), it faces risks of resource concentration, price fluctuations, and ethical constraints on mining, which seriously restrict the sustainable development of the industry.

[0003] Cobalt-free cathode material LiNi x Mn 1-x O2, with its abundant resources, low cost, and high theoretical capacity, is considered an ideal alternative. However, materials prepared using traditional solid-state methods and sol-gel methods suffer from irreversible high capacity (first-time effect <80%) and rapid capacity decay (100-week retention <70%). The root cause lies in the strong Li... + / Ni 2+ Mixing effect (mixing degree >10%). Existing modification technologies such as fine heat treatment, oxygen-enriched sintering, and heteroatomic doping all have significant limitations: fine heat treatment has a small temperature control tolerance (±5℃), resulting in poor process stability; oxygen-enriched sintering relies on special high-pressure equipment, causing costs to surge by more than 200%; heteroatomic doping, due to uneven distribution (composition deviation >5%), leads to deterioration of lattice distortion consistency.

[0004] Therefore, developing a synthesis method that can avoid high-temperature lattice distortion and precisely control cation occupancy has become a key path to overcome the bottleneck of industrialization of cobalt-free layered oxides. Summary of the Invention

[0005] The technical problem to be solved by this invention is to provide a cobalt-free lithium-ion layered oxide cathode material and its preparation method that exhibits significantly suppressed lithium-nickel mixing, excellent structural stability, and outstanding cycle performance, thereby overcoming the limitations of traditional high-temperature synthesis methods due to the influence of Li... + / Ni 2+The problem of cation mixing caused by similar ionic radii and rapid migration.

[0006] The technical solution adopted by this invention to solve its technical problem is:

[0007] A layered oxide material with high cycle stability, its chemical formula is: Li a Na b Ni x Mn 1-x O2, where 0 <x<1,0.90≤a≤1,0≤b≤0.1。

[0008] The preparation method of the layered oxide material with high cycle stability includes the following steps:

[0009] S1. Precursor Preparation: Prepare a layered oxide precursor, wherein the chemical formula of the layered oxide is NaNi. x Mn 1- x O2, where 0 <x<1;

[0010] S2. The precursor is mixed with a first lithium source, and then the lattice sites of Li are subjected to Li ion exchange by at least one of molten salt ion exchange, solid-phase ion exchange, and liquid-phase ion exchange. + / Na + Substitution yields an intermediate;

[0011] S3. After cleaning the intermediate, the solid and liquid are separated and dried to obtain a layered oxide material with high cycle stability.

[0012] The method of this invention first synthesizes a sodium ion precursor NaNi with a complete layered structure. x Mn 1-x O2 (its large radius Na) + Effectively blocks Ni 2+ Interlayer migration), and then through topology-guided Li + / Na + Lattice substitution reaction to convert precursors into LiNi in molten salt / liquid / solid media. x Mn 1-x O2 target material. This method involves a liquid-solid reaction process, characterized by fast reaction rate and low temperature. In material synthesis, it can utilize the similarity and concentration difference of ions to achieve the purpose of directional control of ion migration and reducing synthesis conditions.

[0013] This invention utilizes lattice site-selective Li + / Na + The layered oxide material was prepared by a substitution reaction, partly due to the NaNi x Mn 1-xThe synthesis of O2 layered precursors is not sensitive to temperature, Na + with Ni 2+ The radius difference is large, Ni 2+ Difficult to enter Na + The layered structure can be maintained at different synthesis temperatures, reducing the difficulty of synthesizing layered transition metal oxide materials and overcoming the temperature sensitivity of traditional synthesis methods. On the other hand, by adjusting the molar ratio of Li / Na, the time and temperature of ion exchange, the proportion and rate of ion exchange can be further controlled, thereby desensitizing the material to the synthesis temperature and regulating the lithium-nickel mixture from both the synthesis and use processes.

[0014] In some embodiments, in step S2, the molar ratio of Li in the first lithium source to the precursor is 5-15:1.

[0015] In some embodiments, the first lithium source is at least one of lithium oxide, hydroxide, carbonate, nitrate, and acetate.

[0016] In some embodiments, the method for molten salt ion exchange in step S2 is as follows:

[0017] The precursor, the first lithium source, and the molten salt are mixed and heated to 220-320℃ and kept at that temperature for 5-11 hours.

[0018] In some embodiments, the molten salt is at least one of lithium chloride and lithium nitrate.

[0019] In some embodiments, in step S1, the layered oxide precursor is synthesized using any one of the following methods: high-speed ball milling, solvothermal, hydrothermal, condensation reflux, or solid-state sintering.

[0020] In some embodiments, the solid-state sintering method specifically involves: mixing a second lithium source, a nickel source, and a manganese source, then heating the mixture to 300-450°C for pre-sintering for 3-8 hours; followed by heating to 700-850°C for sintering for 10-15 hours to obtain the layered oxide. In some embodiments, the second lithium source is at least one of lithium oxide, hydroxide, carbonate, nitrate, and acetate; the nickel source is at least one of nickel oxide, hydroxide, carbonate, nitrate, acetate, and chloride; and the manganese source is at least one of manganese oxide, hydroxide, carbonate, nitrate, acetate, and chloride.

[0021] In some embodiments, in step S3, the solid-liquid separation is centrifugal separation; the drying is oven drying; the number of centrifugations is 2 to 6, the rotation speed is 3000 to 7000 r / min, the centrifugation time for each centrifugation is 2 to 15 min, the drying temperature is 60 to 120℃, and the drying time is 15 to 30 h.

[0022] The present invention also provides the application of the above-mentioned layered oxide material as a positive electrode active material.

[0023] The present invention also provides a cathode material, wherein the cathode material comprises the above-mentioned layered oxide material.

[0024] The present invention also provides an electrochemical energy storage device, which includes the above-mentioned positive electrode material.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] This invention presents a cobalt-free lithium-ion layered oxide cathode material with high cycle stability, low Li / Ni mixing, good structural stability, and excellent cycle stability.

[0027] The method for preparing cobalt-free lithium-ion layered oxide cathode material provided by the present invention can prepare cobalt-free lithium-ion layered oxide cathode material with high cycle stability, low Li / Ni mixing and good structural stability.

[0028] The preparation method of this invention is simple and easy to control, with low raw material cost and low synthesis difficulty. It can prepare a layered transition metal oxide cathode material for lithium-ion batteries with significantly improved lithium-nickel hybridization, good material structure stability, and excellent cycle performance.

[0029] The preparation method of this invention can desensitize the material to the synthesis temperature, reduce the synthesis difficulty of layered transition metal oxide cathode materials for lithium-ion batteries, and overcome the temperature sensitivity of traditional synthesis methods. This is achieved by first synthesizing layered sodium-ion materials and then selectively synthesizing Li-ion materials at lattice sites. + / Na + The substitution reaction prepares lithium-ion battery cathode materials, which can effectively suppress Li / Ni mixing at the source. Attached Figure Description

[0030] Figure 1 The LiNi obtained in Example 1 0.5 Mn 0.5 XRD pattern of O2 material;

[0031] Figure 2 The LiNi obtained in Example 1 0.5 Mn 0.5 SEM image of O2 material;

[0032] Figure 3 The LiNi obtained in Examples 1, 2, 3 and Comparative Example 1 0.5 Mn 0.5 Comparison of charge-discharge specific capacity of O2 material at 0.1C current density;

[0033] Figure 4 The LiNi obtained in Example 1 0.5 Mn 0.5 Electrochemical cycling performance of O2 material at 1C current density. Detailed Implementation

[0034] Numerous specific details are set forth in the following description to provide a full understanding of the invention. However, the invention can be practiced in many other ways different from those described herein, and similar modifications can be made by those skilled in the art without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0036] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; the reagents and materials described are commercially available unless otherwise specified.

[0037] Example 1

[0038] The chemical formula of the layered oxide material in this embodiment is: Li 0.98 Na 0.01 Ni 0.5 Mn 0.5 O2;

[0039] The method for preparing the layered oxide material with high cycle stability in this embodiment includes the following steps:

[0040] S1. Precursor preparation: according to NaNi 0.5 Mn 0.5 Weigh out the corresponding mass of Ni based on the stoichiometric coefficient of O2. 0.5 Mn 0.5 (OH)2 and Na2CO3 were ball-milled in a ball mill jar with an excess of 3 times the volume of anhydrous ethanol as a dispersant at a speed of 300 rpm for 5 h; then the mixture was dried in a forced-air drying oven at a temperature of 80 °C for 12 h to obtain the dried product.

[0041] Then, the dried product was placed in a muffle furnace and heated to 450°C at a rate of 5°C / min, held for 5 hours, and then heated to 900°C for sintering for 15 hours. After that, it was naturally cooled in the furnace to obtain NaNi. 0.5 Mn 0.5 O2;

[0042] S2, Weigh out a mixture of molten salt (88% LiNO3 + 12% LiCl) and Na in a molar ratio of 10:1. 0.99 Ni 0.5 Mn 0.5 O2 precursor was placed in a mortar and manually ground for 1 hour in a glove box filled with argon gas. The uniformly mixed material was placed in a muffle furnace and heated to 300°C at a rate of 5°C / min and held for 5 hours. The material was then cooled with the furnace to obtain a block material.

[0043] S3. Dissolve the block material in a mixed solution of deionized water and anhydrous ethanol (volume ratio of water to anhydrous ethanol 3:1), stir for 20 min, and then centrifuge at a speed of 3000 r / min for 7 min each time, for a total of 4 centrifugations; then place it in a forced-air drying oven to dry at a temperature of 80℃ for 15 h to obtain a layered oxide material.

[0044] The layered oxide material obtained in this embodiment was subjected to ICP testing, and the results are shown in Table 1.

[0045] Table 1. ICP-OES test results of layered oxide materials before and after ion exchange in Example 1.

[0046]

[0047] The layered oxide material obtained after ion exchange in this embodiment was characterized by XRD and SEM. The results are shown in [reference needed]. Figure 1 and Figure 2 .

[0048] like Figure 1 As shown, after ion exchange, the material forms a layered oxide with a lithium-nickel mixture as low as 3.26%, far lower than that of LiNi prepared by traditional synthesis methods. 0.5 Mn 0.5 The degree of lithium-nickel mixing in O2 materials.

[0049] like Figure 2 As shown, it can be seen that the material consists of primary particles in the form of blocks and flakes agglomerated into secondary particles in the form of spherical shapes.

[0050] The layered oxide material obtained by ion exchange in this embodiment is used as the active material to prepare the positive electrode material, and then assembled into a coin cell. The specific steps are as follows:

[0051] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode active material was weighed, and 0.01g of acetylene black as conductive agent and 0.01g of polyvinylidene fluoride as binder were weighed. They were placed in a mortar and mixed. After being mixed evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, it was coated on aluminum foil to form a positive electrode sheet. In a glove box under an inert protective atmosphere, lithium metal was used as the negative electrode to assemble a CR2032 coin cell.

[0052] After the assembled battery was left to stand for 12 hours, its electrochemical performance was tested. The results are shown in [link to results]. Figure 3 and Figure 4 .

[0053] like Figure 3 and Figure 4 As shown, the layered oxide material obtained after ion exchange, as the active material, has a first-cycle discharge specific capacity of 194.17 mAh / g at 0.1C (1C = 200 mAh / g); and retains 94% of its capacity after 400 cycles at a 1C discharge rate.

[0054] Example 2

[0055] The chemical formula of the layered oxide material in this embodiment is: Li 0.96 Na 0.07 Ni 0.49 Mn 0.51 O2;

[0056] The method for preparing the layered oxide material with high cycle stability in this embodiment includes the following steps:

[0057] S1, according to NaNi 0.5 Mn 0.5 Weigh out the corresponding mass of Ni based on the stoichiometric coefficient of O2. 0.5 Mn 0.5 (OH)2 and NaOH were manually ground and mixed evenly in a mortar to obtain a mixed product;

[0058] Then, the obtained mixture was placed in a muffle furnace and heated to 400°C at a rate of 5°C / min, held for 3 hours, and then sintered at 700°C for 12 hours. After that, it was naturally cooled in the furnace to obtain Na. 0.98 Mn 0.49 Ni 0.51 O2;

[0059] S2, Weigh out a mixture of molten salt (88% LiNO3 + 12% LiCl) and Na in a molar ratio of 15:1. 0.98 Mn 0.49 Ni 0.51The O2 precursor was placed in a mortar and manually ground for 1 hour in an argon-filled glove box. The uniformly mixed material was then placed in a muffle furnace and sintered at 280°C for 5 hours at a rate of 5°C / min, followed by furnace cooling.

[0060] S3. Dissolve the block material in a mixed solution of deionized water and anhydrous ethanol (volume ratio 3:1), stir for 20 min and then centrifuge at a speed of 3000 r / min for 7 min each time, for a total of 4 centrifugations; then place it in a forced-air drying oven to dry and obtain layered oxide material at a drying temperature of 80℃ for 15 h.

[0061] The materials obtained in this embodiment were subjected to ICP testing, and the results are shown in Table 2.

[0062] Table 2. ICP-OES test results of materials before and after ion exchange.

[0063]

[0064] The layered oxide material obtained by ion exchange in this embodiment is used as the active material to prepare the positive electrode material, and then assembled into a coin cell. The specific steps are as follows:

[0065] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as conductive agent and 0.01g of polyvinylidene fluoride as binder were weighed. They were placed in a mortar and mixed. After being mixed evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, it was coated on aluminum foil to form a positive electrode sheet. In a glove box under an inert protective atmosphere, lithium metal was used as the negative electrode to assemble a CR2032 coin cell.

[0066] After the assembled battery was left to stand for 12 hours, its electrochemical performance was tested. The results are shown in [reference needed]. Figure 3 .

[0067] like Figure 3 As shown, the layered oxide material obtained after ion exchange, as the active material, has a first-cycle discharge specific capacity of 194.61 mAh / g at 0.1C (1C = 200 mAh / g).

[0068] Example 3

[0069] The chemical formula of the layered oxide material in this embodiment is: Li 0.92 Na 0.09 Ni 0.49 Mn 0.51 O2

[0070] The method for preparing the layered oxide material with high cycle stability in this embodiment includes the following steps:

[0071] S1, according to NaNi 0.5 Mn 0.5 Weigh out the corresponding mass of Ni based on the stoichiometric coefficient of O2. 0.5 Mn 0.5 (OH)2 and NaOH were mixed evenly by manual grinding in a mortar.

[0072] Then, the obtained mixture was placed in a muffle furnace and heated to 400°C at a rate of 5°C / min, held for 3 hours, and then sintered at 700°C for 12 hours. After that, it was naturally cooled in the furnace to obtain Na. 0.98 Mn 0.49 Ni 0.51 O2;

[0073] S2. Weigh out LiOH and Na in a molar ratio of 10:1. 0.98 Mn 0.49 Ni 0.51 O2 was added to deionized water to prepare a 4M LiOH solution, which was then transferred to a polytetrafluoroethylene liner and magnetically stirred to mix thoroughly. The mixture was then sealed in a hydrothermal reactor and subjected to ion exchange at 200℃ for 8 hours. After filtration, centrifugation and drying, the ion exchange product was obtained.

[0074] S3. After ion exchange, in order to remove excess lithium salt and the exchanged Na + The product was soaked in 200ml of deionized water and stirred for 20min, then filtered and centrifuged. Finally, it was dried at 60℃ for 24h to obtain the layered oxide material.

[0075] The materials obtained in this embodiment were subjected to ICP testing, and the results are shown in Table 3.

[0076] Table 3. ICP-OES test results of materials before and after ion exchange.

[0077]

[0078] The layered oxide material obtained by ion exchange in this embodiment is used as the active material to prepare the positive electrode material, and then assembled into a coin cell. The specific steps are as follows:

[0079] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as conductive agent and 0.01g of polyvinylidene fluoride as binder were weighed. They were placed in a mortar and mixed. After being mixed evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, it was coated on aluminum foil to form a positive electrode sheet. In a glove box under an inert protective atmosphere, lithium metal was used as the negative electrode to assemble a coin cell of model CR2032.

[0080] After the assembled battery was left to stand for 12 hours, its electrochemical performance was tested. The results are shown in [reference needed]. Figure 3.

[0081] like Figure 3 As shown, the obtained cathode material has a first-cycle discharge specific capacity of 184.51 mAh / g at 0.1C (1C = 200 mAh / g).

[0082] Comparative Example 1

[0083] This embodiment uses a high-temperature solid-state method to prepare layered oxides LiMn. 0.5 Ni 0.5 O2, the specific steps include:

[0084] (1) Weigh out LiOH (5% excess) and Ni according to the stoichiometric ratio. 0.5 Mn 0.5 (OH)₂ was activated by low-speed ball milling in a ball mill jar using anhydrous ethanol as the solvent at a speed of 300 rpm for 5 hours. It was then dried in a forced-air drying oven at 80°C for 12 hours.

[0085] (2) The dried product was placed in a muffle furnace and heated to 300°C at a rate of 5°C / min. After holding at 300°C for 5 hours, the temperature was increased to 700°C and sintered for 12 hours. Then, the product was allowed to cool naturally in the furnace to obtain LiMn. 0.5 Ni 0.5 O2.

[0086] The layered oxide material obtained by heat treatment in this comparative example was used as the active material to prepare the positive electrode material, and then assembled into a coin cell. The specific steps are as follows:

[0087] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as conductive agent and 0.01g of polyvinylidene fluoride as binder were weighed. They were placed in a mortar and mixed. After being mixed evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, it was coated on aluminum foil to form a positive electrode sheet. In a glove box under an inert protective atmosphere, lithium metal was used as the negative electrode to assemble a coin cell of model CR2032.

[0088] After the assembled battery was left to stand for 12 hours, its electrochemical performance was tested. The results are shown in [reference needed]. Figure 3 .

[0089] like Figure 3 As shown, the obtained cathode material has a first-cycle discharge specific capacity of 165.7 mAh / g at 0.1C (1C = 200 mAh / g).

[0090] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0091] The above-described embodiments are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the contents of the claims.

Claims

1. A layered oxide material with high cycle stability, characterized in that, The chemical formula is: Li a Na b Ni x Mn 1-x O2, where 0 <x<1,0.90≤a≤1,0≤b≤0.1。 2. A method for preparing a layered oxide material with high cycle stability as described in claim 1, characterized in that, Includes the following steps: S1. Precursor Preparation: Prepare a layered oxide precursor, wherein the chemical formula of the pre-layered oxide is NaNi. x Mn 1-x O2, where 0 <x<1; S2. The precursor is mixed with a first lithium source, and then the lattice sites of Li are subjected to Li ion exchange by at least one of molten salt ion exchange, solid-phase ion exchange, and liquid-phase ion exchange. + / Na + Substitution yields an intermediate; S3. After cleaning the intermediate, the solid and liquid are separated and dried to obtain a layered oxide material with high cycle stability.

3. The method for preparing a layered oxide material with high cycle stability according to claim 2, characterized in that, In step S2, the molar ratio of Li in the first lithium source to the precursor is 5-15:

1.

4. The method for preparing a layered oxide material with high cycle stability according to claim 2 or 3, characterized in that, The first lithium source is at least one of lithium oxide, hydroxide, carbonate, nitrate, and acetate.

5. The method for preparing a layered oxide material with high cycle stability according to claim 2 or 3, characterized in that, In step S2, the method for molten salt ion exchange is as follows: The precursor, the first lithium source, and the molten salt are mixed and heated to 220-320℃ and kept at that temperature for 5-11 hours.

6. The method for preparing a layered oxide material with high cycle stability according to claim 2 or 3, characterized in that, In step S1, the layered oxide precursor is synthesized using any one of the following methods: high-speed ball milling, solvothermal, hydrothermal, condensation reflux, or solid-state sintering.

7. The method for preparing a layered oxide material with high cycle stability according to claim 6, characterized in that, The solid-state sintering method specifically involves mixing a second lithium source, a nickel source, and a manganese source, then heating the mixture to 300-450°C for pre-sintering for 3-8 hours; and then heating the mixture to 700-850°C for sintering for 10-15 hours to obtain the layered oxide.

8. The application of the layered oxide material according to claim 1 as a positive electrode active material.

9. A positive electrode material, characterized in that, Includes the layered oxide material as described in claim 1.

10. An electrochemical energy storage device, characterized in that, Includes the cathode material as described in claim 9.

Citation Information

Cited By

  • Full-manganese-based lithium-rich positive electrode material with novel superlattice topological stack

    CN121260789A

  • A full-manganese-based lithium-rich cathode material with superlattice topological stacking

    CN121260789B